INVERSION - Rajabova Madina Abdusamatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This article explores the phenomenon of inversion in linguistics, focusing on its usage, types, and functions across different languages. The study includes a detailed literature analysis, methods used for data collection, results obtained from the analysis, a discussion of the findings, and conclusions with suggestions for further research.